Cultivating Feminist Hermeneutics As The Interpretation Of Al-Qur'an: A Comparative Study Between Asghar Ali Engineer And Muhammad Al-Ghazali - Haidar Masyhur Fadhil (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2023)
This paper examines the ideas and thoughts of Asghar Ali Engineer and Muhammad al-Ghazali, especially regarding the reconstruction of their tafsir methodology related to gender verses and the application and theoretical implications of the method they built. As fighters for liberation theology and fighters for women's rights, both figures try to defend women by interpreting al-Qur’an based on gender equality and trying to criticize the interpretation of classical scholars who are atomistic. This article is a comparative study based on the works of Asghar Ali Engineer and Muhammad al-Ghazali. At the same time, the approach taken is using descriptive-analytical. In this study, at least I found that Asghar Ali Engineer uses three essential methods: historical, sociological-anthropological, and philosophical. On the other hand, al-Ghazali uses a more traditionalist-progressive approach: Reading text and reality, contextualizing the meaning of the text further, and separating dynamic verses from static verses. Furthermore, applying feminist hermeneutics to the verses of al-Qur’an carried out by the two figures strongly opposes discrimination and injustice against women.